Proceedings of the 8th International Conference of Asian Association of Indigenous and Cultural Psychology (ICAAIP 2017) 2018
DOI: 10.2991/icaaip-17.2018.59
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Level with Health Care Quality at Dental Hospital of Hasanuddin University

Abstract: Abstract--Patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…The relationship between the patient and the dentist, the qualifications of the doctor, the conditions of treatment and its accessibility shape the patient's perception of the quality of dental care [9].…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the patient and the dentist, the qualifications of the doctor, the conditions of treatment and its accessibility shape the patient's perception of the quality of dental care [9].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the study also revealed that infrastructure has significantly correlated to patient satisfaction. Women want better care, more privacy during visit hours, and less pain [21,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…Communication errors between the service provider and the patient may result in a medical error affecting the patient's condition. The communication-centered approach between the service provider and the patient is considered a good strategy in creating relationships with patients, and is considered a key to improving the quality of health care [25,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Rural patients were generally more satisfied with health services than urban and suburban populations. It can be explained that urban residents have the possibility to choose professional care from health care providers [4,[19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%